Metode Penulisan Artikel Telaah Literatur - Anung Ahadi Pradana; Muhammad Chandra; Ismail Fahmi; Casman; Alfunnafi' Fahrul Rizzal; Nani Asna Dewi; Nur’aini (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2021)
Lecturers in Indonesia only focus on original research in implementing Tri Dharma of Higher Education. A literature review has not been optimally used because of the lack of guidance. This article aimed to describe what a literature review is and how to compile good literature. This article is a simple literature review. The keywords used were "literature review", "literature review", "scoping review", and "systematic review" from the databases of Google Scholar, ResearchGate, SpringerLink, and EBSCO. The search resulted in 10 selected articles that discussed the review literature from the definition, type, stages of making a literature review. Writing a good literature review must be done starting from determining the source of the article to the understandable conclusions. To reduce the risk of errors in making a literature review, we must pay attention to the guidelines to obtain a literature review with high quality of evidence and low bias.